Implementasi Nilai-Nilai Kebangsaan dalam Menangkal Disinformasi di Era Digital: Upaya Memperkuat Demokrasi, Kesamaan Derajat, dan Ketaatan Hukum Menuju Indonesia Emas 2045 - Dani Setiadarma; Laili Fitriyah; Tri Satria Muhammad; Ferdi Setiawan (Jurnal Ilmu Sosial dan Humaniora, 2026)
The advancement of digital technology has accelerated the flow of information but has also increased the spread of disinformation, which threatens democracy, equality, adherence to the rule of law, and national resilience. This conceptual, literature-based article aims to analyze the implementation of national values ​​derived from the 1945 Constitution of the Republic of Indonesia as a strategy to counter disinformation in the pursuit of "Golden Indonesia 2045." The study employs a critical analysis of relevant scholarly literature, legislation, government documents, and prior research findings. The results indicate that the value of democracy is realized through critical and responsible public participation in the digital space; the value of equality is upheld by respecting every citizen's right to access and convey information fairly and without discrimination; and the value of adherence to the rule of law is manifested through compliance with the constitution, legislation, and digital media ethics. Strengthening media and information literacy, ensuring consistent law enforcement, and fostering multi-stakeholder collaboration are crucial strategies for building a healthy digital space, reinforcing national resilience, and supporting the realization of Golden Indonesia 2045.